Gender as Determinant Factor of Routes for Registered Unemployment Exit - Beata Bieszk-Stolorz (Institute of Economic Research (IER), 2017)
Numerous studies show that men's and women's situation on the labour market differs. Women's disadvantageous position on the labour market has been confirmed by statistical data. Finding a job is just one of many causes why an individual is crossed out from the labour office register. The registered unemployed can retire, apply for invalidity pension, receive early retirement benefits or start full time studies. One of the most common causes of de-registering is the unemployed person's unjustified refusal to accept a job offer. The above causes are regarded as competing risks of various kinds. The purpose of this article is to assess the effect of the unemployed individual's gender on the probability and intensity of de-registering from the labour office lists due to finding a job, de-registering or other causes. The study made use of the survival analysis methods. The assessment of the probability of de-registration due to a specific cause was made by means of the cumulative incidence function. The intensity of de-registration was tested with the Lunn-McNeil model. Differences in the effect of gender on the de-registration possibility were tested with the use of Gray's test. The study was based on individual data of people registered by the Labour Office in Szczecin. Among women, job-finding was the most common cause of de-registration, followed by the removal from the register. In the case of men the order was reversed, the most probable de-registration cause was the removal, followed by job-finding. The remaining causes were of marginal significance, both for men and women. Women took up a job more intensively than men and were less intensively removed from the register. The differences between males and females in the intensities of de-registering due to the remaining causes were not statistically relevant.
Keywords: C41; J64; 330; competing risk; cumulative incidence function; the Lunn-McNeil model; unemployment; gender